The complex superstructure in Mg1-xAlxB2 at x approximate to 0.5 - Zandbergen, H; Wu, M; Jiang, H; Hayward, M; Haas, M; Cava, R (2002)
Electron diffraction and high resolution microscopy have been performed on Mg1-xAlxB2 with x≅0.5. This composition displays a superstructure with a repeat period of exactly 2c along the c-axis and about 10 nm in the a-b plane. The superstructure results in ring-shaped superreflections in the diffraction pattern. Irradiation by a strong electron beam results in a loss of the superstructure and a decrease of about 1% in the c lattice parameter. In situ heating and cooling on the other hand showed that the superstructure is stable from 100 to 700 K. Possible origins for the superstructure are proposed. © 2002 Published by Elsevier Science B.V.